Proteomic analysis of Malaysian Horseshoe crab (Tachypleus gigas) hemocytes gives insights into its innate immunity host defence system and other biological processes. - Ismail Abiola Adebayo; Mohd Afiq Hazlami Habib; Maria E Sarmiento; Armando Acosta; Nik Soriani Yaacob; Mohd Nazri Ismail (PLoS ONE, 2022)
Horseshoe crabs are one of the most studied invertebrates due to their remarkable innate immunity mechanism and biological processes. In this work, the proteins of the lipopolysaccharides (LPS)-stimulated and non-stimulated hemocytes of Malaysian Tachypleus gigas were profiled using LC-MS/MS. A total of 154 proteins were identified in both types of samples. Additionally, seventy-seven proteins were commonly found in both conditions, while 52 and 25 proteins were uniquely found in the LPS-stimulated and non-stimulated hemocytes, respectively. ATP-dependent energy-generating proteins such as actins and BLTX actin-related proteins were detected in both stimulated and non-stimulated T. gigas hemocytes, but more of such proteins were found in the former type. Proteins such as tachylectin-2, coagulogen, c-reactive proteins, histones, hemocyanin, and DNA polymerase, which play key roles in the organism's innate immunity, were differentially expressed in the hemocytes following LPS challenge. In conclusion, the proteins identified in the hemolymph of T. gigas are vital for the organism's molecular functions, biological processes, and activation of innate immunity.